Maternal representations of pregnant women and baby care in the context of COVID-19 (Research, Society and Development, 2023)
Maternal representations consist of a set of ideas, fears, changes, thoughts, expectations, desires, sensations and perceptions of the pregnant woman about the baby, about herself as a mother and her support network. The first mother-baby relationships are of great importance for child development and require several adaptations from the woman and her family. This study aimed to analyze the perceptions about the maternal representations of 15 pregnant women who underwent prenatal care at a Basic Health Unit (UBS) in the interior of Maranhão. This is a qualitative, exploratory and descriptive study, in which the sociodemographic profile of women and maternal representations during pregnancy were traced. Most of the interviewees had more than two pregnancies, aged between 21 and 30 years, completed high school, stable union and no employment relationship. Pregnancy involves moments of transformation and sensitivity due to the changes caused during this period. Family relationships contributed in different ways, depending on the context in which the pregnant woman was inserted, making the support network during the gestation period essential, where the woman biologically and psychologically undergoes changes.